Complete Genome Sequence of Staphylococcus lugdunensis Strain HKU09-01 - Tse, Herman (American Society for Microbiology (ASM), 2010)
Staphylococcus lugdunensis is a member of the coagulase-negative staphylococci and commonly found as part of the human skin flora. It is a significant cause of catheter-related bacteremia and also causes serious infections like native valve endocarditis in previously healthy individuals. We report the complete genome sequence of this medically important bacterium.